Modification of ABA VB Therapy Methods with Pomodoro to Improve Verbal Communication in Autism Children - Apriyanti, Vina Pemila (Angstrom Centre of Education, 2022)
Autism is a pervasive developmental disorder in children characterized by disturbances and delays in cognitive, language, behavioral, and social interactions. Verbal Behavior approach is one of the methods of ABA which is used to increase desired behavior and reduce unwanted problems, while pomodoro is a timing technique. This article describes the implementation of an intervention program for children with autism, this program modifies ABA VB therapy and combines it with a timing technique, namely POMODORO. The author implemented the program for 4 meetings. At the first meeting until the fourth meeting there was an increase in the child's verbal ability although it was not so visible. The intervention program developed by the author had good results, because at the first meeting the results were already visible. This intervention should be done repeatedly or routinely so that children get used to it and get maximum results.